The genome of Epiperipatus biolleyi (Peripatidae), a Costa rucan onychophoran - Mora, Marielos (Universidad de Costa Rica, 1996)
Cytologic studies of Epiperipatus biolleyi, a Costa Rican onychophoran, reveal the presence of a large genome (C-value=4.3 pg/C) with many chromosomes, and a bimodal karyotype. Analysis of maje meiosis indicates lha! all chromosomes are rod-shaped, without distinct primary constrictions. Two large bivalents are consistently associated with nucleoli. Meiosis proceeds through the pachytene stage, with a few thick bivalents that break up into many small and a few large chromosomes at the diplotene stage. At metaphase the rod-shaped bivalents seem to be pulled from the telomeres into opposite poles of the spindle, lacking well defined kinetochores. DNA isolated from E. biolleyi presents a complex profile with very low GC-content in isopycnic cesium gradients. Digestion with restriction enzymes produces a homogenous spread of molecules, except with Rae III, Hind m and Bgl n, which generate distinct bands of fluorescence. A Bgl n repeat of 1.9 Kb, has been cloned for evolutionary studies. Based on these results, many repetitive DNA familíes should be found in this genome.